Discrete Design Optimization of Small Open Type Dry Transformers - Raju Basak; Arabinda Das; Ajay Sensarma; Amar Nath Sanyal (Institute of Advanced Engineering and Science, 2012)
Transformers of small ratings have a wide field of application. They are generally designed and fabricated using standard stampings available in the market. The design is made according to guidelines given in text-books. But such guidelines do not yield a cost-optimal solution. It may even fail to give a feasible solution if design variables are not properly chosen. This paper presents a method to get the cost-optimal solution subject to usual design constraints. The line of approach is completely different from that given in the standard text-books. Computer programs have been developed for finding out the cost-optimal design using standard stampings and case studies have been made on its basis.